2011
DOI: 10.1164/rccm.201102-0227oc
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and Survival in Four Cohorts with Potentially Predisposing Diseases

Abstract: Rationale: Time series studies have reported associations between ozone and daily deaths. Only one cohort study has reported the effect of long-term exposures on deaths, and little is known about effects of chronic ozone exposure on survival in susceptible populations. Objectives: We investigated whether ozone was associated with survival in four cohorts of persons with specific diseases in 105 United States cities, treating ozone as a time varying exposure. Methods: We used Medicare data , and constructed coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 37 publications
(43 reference statements)
4
55
1
Order By: Relevance
“…Some analyses found associations with respiratory mortality and some with all-cause and cardiopulmonary mortality. However, the Zanobetti & Schwartz (2011) study together with toxicological studies (see Question B1) provide further support for the effects of long-term exposures to ozone.…”
Section: Ozone Averaging Time Of Exposurementioning
confidence: 83%
See 3 more Smart Citations
“…Some analyses found associations with respiratory mortality and some with all-cause and cardiopulmonary mortality. However, the Zanobetti & Schwartz (2011) study together with toxicological studies (see Question B1) provide further support for the effects of long-term exposures to ozone.…”
Section: Ozone Averaging Time Of Exposurementioning
confidence: 83%
“…Since 2005, several cohort analyses (Table 1) have been published; together they suggest an effect of long-term exposure to ozone on mortality, at least for respiratory or cardiorespiratory mortality, especially in people with potential predisposing conditions (Lipfert et al, 2006;Krewski et al, 2009;Jerrett et al, 2009a;Smith KR et al, 2009;Zanobetti & Schwartz, 2011). Generally, these studies do not include ozone exposure from cohort entry to death, and some use limited monitoring data.…”
Section: Epidemiological Studies Of Long-term Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…A further study by Jerrett et al (2009) using the same cohort found unstable risk estimates for ozone and all-cause, cardiopulmonary and cardiovascular mortality, with only respiratory mortality being associated with ozone after adjustment for PM 2.5 . For a more detailed discussion of these and other recent cohort studies (Smith et al, 2009;Zanobetti and Schwartz, 2011;Lipsett et al, 2011) than space here permits, the reader is referred to the REVIHAAP report.…”
Section: Healthmentioning
confidence: 99%